A systematic review and agenda for using alternative water sources for consumer markets in Australia. (15th June 2016) - Adapa, Sujana; Bhullar, Navjot; de Souza, Simone Valle
Abstract: Water scarcity is a common phenomenon identified in many countries and Australia is no exception. Australia is the driest continent and has been prone to severe and prolonged drought conditions in recent years. Yet the quality of drinking water is taken for granted in Australia and existing evidence showcases a huge setback in the uptake of alternative sources of water by Australian consumer markets. In order to understand the existing situation and identify the barriers and opportunities associated to alternative sources of water, a systematic review of existing research in the area of alternative sources of water for consumer markets has been conducted. The importance of water as a precious resource to sustain human life and a review of relevant literature of alternative sources of water (mainly recycled and desalinated) and issues surrounding centralised and decentralised water systems are discussed. Results are reported from extant research upon public acceptance of consumer satisfaction, contextual factors, demographic variables and perceived benefits and costs associated with the intention to adopt, and the adoption and use of recycled and desalinated water. Our findings highlight the limitations of prior studies and outline the strategic importance of a much needed marketing-related 7Ps research framework for promoting the consumption and use of alternative water sources within the Australian consumer market. Similarly the discussion highlights the relative importance of investing in various marketing interventions in enhancing Australian consumer markets awareness, acceptance and uptake of alternative sources of water. The uptake of alternative sources of water amongst Australian consumer markets is envisaged to be enhanced through critical understanding of the various aspects associated to product, price, place, promotion, people, process and physical evidence. In sum, the present systematic review provides the most relevant issues surrounding the usage of alternative sources of water within the Australian consumer market; elicits the importance of public acceptance, consumer satisfaction, demographic variables, contextual factors apart from benefits and barriers to recycled water; and proposes a research framework that needs to be addressed by future research. Highlights: A systematic review of published literature on the public usage of alternative sources of water is conducted. The critical factors that hinder the acceptance and consumption of alternative sources of water are identified. The relevance of various marketing interventions for the uptake of alternative sources of water is outlined. Marketing-related 7Ps research framework is proposed. Avenues for further investigation are suggested.